Low-cost geological solutions for communities in high-risk areas - Moreira, Éder; de Moura Silva Gonçalves de Macedo, Danilo; Araújo de Souza, Henrique; Almeida Vilela, Daniel; Oliveira Salvato, Pablo; Rodrigues de Souza, Pablo; Coelho Fabrino Filho, Leonardo; Moura Gonçalves, Myllena; Silva Oliveira, Ana Laura (Guará Journal, 2025)
The project is underway at the Alegre campus of the Federal University of Espírito Santo, as part of the Geological Solutions for Rock and Soil Characterization Analysis Program. This extension program focuses on studying low-cost solutions for stabilizing slopes. Expected results include the planting of vetiver grass in areas of high geological risk and the construction of drainage channels to direct rainwater, with active community participation. The work aims to provide valuable input to the communities, educating them about geotechnical issues and promoting environmental awareness. The extension action promotes safety and environmental understanding for local residents, in addition to identifying measures to combat erosion and stabilize slopes, such as the planting of vetiver grass, which has proven to be erosion-resistant and contributes to soil stabilization. The communities of Alegre are involved in the process, participating in meetings and collaborating on the planting, resulting in visible progress, such as reduced runoff and slope stabilization.